The Issue of Control in Jail: The Effects of Professionalism, Detainee Control, and Administrative Support on Job Stress, Job Satisfaction, and Organizational Commitment among Jail Staff - Paoline, Eugene A. (American journal of criminal justice, 2012)
Jails are important, yet understudied, components of the American criminal justice system. While most research on correctional personnel has focused on prisons, a growing body of work is beginning to emerge on jails. This is encouraging given the unique circumstances that occur within jail environments (e.g., diversity and mobility of offenders, health issues among detainees, overcrowding, lack of training among staff, etc.). Given these conditions, the staff members who run jails become the glue that holds them together. The following study contributes to this burgeoning area of empirical inquiry by examining a variety of antecedents of job stress, job satisfaction, and organizational commitment among jail personnel. Using survey data collected from a large county correctional system in Orlando, Florida, the findings indicate that staff perceptions of professionalism, detainee control, and administrative support all significantly impact degrees of job stress, job satisfaction, and organizational commitment.